Pharmacological Strategies to Prevent Contrast-Induced Acute Kidney Injury. (26th February 2014) - Pattharanitima, Pattharawin; Tasanarong, Adis
Abstract : Contrast-induced acute kidney injury (CI-AKI) is the most common iatrogenic cause of acute kidney injury after intravenous contrast media administration. In general, the incidence of CI-AKI is low in patients with normal renal function. However, the rate is remarkably elevated in patients with preexisting chronic kidney disease, diabetes mellitus, old age, high volume of contrast agent, congestive heart failure, hypotension, anemia, use of nephrotoxic drug, and volume depletion. Consequently, CI-AKI particularly in high risk patients contributes to extended hospitalizations and increases long-term morbidity and mortality. The pathogenesis of CI-AKI involves at least three mechanisms; contrast agents induce renal vasoconstriction, increase of oxygen free radicals through oxidative stress, and direct tubular toxicity. Several strategies to prevent CI-AKI have been evaluated in experimental studies and clinical trials. At present, intravascular volume expansion with either isotonic saline or sodium bicarbonate solutions has provided more consistent positive results and was recommended in the prevention of CI-AKI. However, the proportion of patients with risk still develops CI-AKI. This review critically evaluated the current evidence for pharmacological strategies to prevent CI-AKI in patients with a risk of developing CI-AKI.